A contribution to energy efficiency in motor-driven systems - Souza, Danilo Ferreira de (2024)
The advancement in the energy efficiency of electric motors is a crucial element for improving efficiency in industrial processes. Electric motors are fundamental to modern society across all sectors of the economy. This thesis first presents historical research on the key elements that have driven changes in electric motor efficiency from 1945 to the present day. The research results demonstrated cumulative performance gains of more than 10% in some cases, while discrepancies were observed between the efficiencies declared by manufacturers on nameplates and the values measured through standardized testing. Brazilian energy efficiency policies were analyzed, demonstrating substantial gains in the efficiency of drive systems and alignment with international standards. Additionally, the thesis explored the impact of Industry 4.0 technologies on the management of building pump systems, presenting promising possibilities for optimization through advanced control and supervision, enabling significant efficiency gains. Furthermore, life cycle studies were conducted to assess the environmental impact of Permanent Magnet Synchronous Motors and Synchronous Reluctance Motors compared to induction motors. These studies indicated that, although more efficient during the use phase, these motors might have a higher environmental impact during production and disposal. The analysis shows that even at the brink of the theoretical limits of electric motor efficiency, the main efficiency bottlenecks lie in the driven load and the system as a whole. Therefore, there is room for improvements in the efficiency of drive systems, especially when considering the total product life cycle. The thesis concludes that there is a critical need to continue exploring technological advancements and to implement stringent regulatory policies that promote energy efficiency and sustainability, in harmony with global sustainable development goals and the growing energy demands. Research gaps for future investigations were identified and presented.